Behavioral forces driving information unraveling - Volker Benndorf; Dorothea Kübler; Hans-Theo Normann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
Information unraveling is an elegant theoretical argument suggesting that private information may be fully and voluntarily surrendered. The experimental literature has, however, failed to provide evidence of complete unraveling and has suggested senders' limited depth of reasoning as one behavioral explanation. In our novel design, decisionmaking is essentially sequential, which removes the requirements on subjects' reasoning and should enable subjects to play the standard Nash equilibrium with full revelation. However, our design also facilitates coordination on equilibria with partial unraveling which exist with other-regarding preferences. Our data confirm that the new design is successful in that it avoids miscoordination entirely. Roughly half of the groups fully unravel whereas other groups exhibit monotonic outcomes with partial unraveling. Altogether, we find more information unraveling with the new design, but there is clear evidence that other-regarding preferences do play a role in impeding unraveling.
Keywords: C72; C90; C91; 330; data protection; inequality aversion; information revelation; level-k reasoning